EFEKTIVITAS PENDEKATAN DAN PENGEMBANGAN KURIKULUM DI SEKOLAH DASAR - Oktaviani, Mutia; Shafa Aulia, Sabrina; Nurmalasari, Ulfi; Iskandar, Sofyan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The effectiveness of the approach and curriculum development in Indonesia can affect the teaching and learning process. With the passage of time, the curriculum often emphasizes the cognitive realm such as the KTSP curriculum, the 2013 curriculum, the competency-based curriculum, and the independent curriculum. The curriculum approach can be the initial process of preparing the curriculum to be in accordance with existing provisions. For the development of the curriculum itself, a series of activities ranging from identifying needs to the preparation and presentation of learning materials by the development team. But unfortunately, there are still teachers who have difficulty implementing the existing curriculum. Therefore, in order to improve the quality of education, curriculum development must be carried out to find out the principles of effective curriculum development for the quality of learning. Through the library research method, researchers found that developing a curriculum can help develop students' abilities, teacher competence, and increase educational relevance. The curriculum developed not only increases the effectiveness of learning, but also creates an education system that is more adaptive to changes and societal needs.